Plasma Cardiotrophin‐1 Levels are Associated With Hypertensive Heart Disease: A Meta‐Analysis. Issue 9 (23rd July 2014) - Song, Kangxing; Wang, Shuxia; Huang, Bihui; Luciano, Amelia; Srivastava, Roshni; Mani, Arya
<x xml:space="preserve">Abstract</x> Cardiotrophin‐1 (CT‐1) is a member of the interleukin 6 cytokine superfamily. Plasma CT‐1 levels have been associated with heart failure and hypertension in small independent studies. Whether plasma CT‐1 levels are associated with progression of hypertensive heart disease is poorly understood. The authors carried out a meta‐analysis using published studies and electronic databases. Relevant data were extracted using standardized algorithms. Additional data were obtained directly from investigators when indicated. A total of 18 studies were included that reported on association between CT‐1 level and hypertension (n=8), cardiac hypertrophy (n=9), and heart failure (HF) (n=10). The serum levels of CT‐1 were significantly higher in patients with hypertension (standard mean difference [SMD], 0.85; 95% confidence interval [CI], 0.64–1.06 fmol/mL), left ventricular hypertrophy (SMD, 0.88; 95% CI 0.60–1.17 fmol/mL), or HF (SMD, 0.66; 95% CI, 0.51–0.80 fmol/mL) compared with controls. Subgroup analysis revealed CT‐1 levels to be highest in patients with hypertension‐induced hypertrophy with HF, followed by patients with hypertension‐induced left ventricular hypertrophy without HF (SMD, 0.52; 95% CI, 0.30–0.75 fmol/mL), patients with hypertension without left ventricular hypertrophy (SMD, 0.67; 95% CI, 0.46–0.88 fmol/mL) as compared with normotensive patients (SMD, 0.74; 95% CI, 10.45–1.04 fmol/mL). Increased plasma CT‐1 levels are associated with risk for HF in hypertensive patients. CT‐1 may serve as a novel biomarker in determining prognosis in hypertensive patients.